Strategic Research Programs in the Area of Technical Innovations – Case Study Analyses - Walaszczyk Ludmiła (Foundations of Management, 2016)
The development of the knowledge-based economy requires undertaking many actions aimed at increasing competitiveness of enterprises. These actions include, among others, the execution of strategic research programs, which are characterized by a great number of levels, a multitude of objectives and results, and high budgets. In order for the program to be managed correctly, it is necessary to have a complex and effective evaluation system dedicated to such types of programs. The article presents a global case study analysis of the evaluation of strategic research programs. The author examines the evaluation criteria and methods used in the evaluation processes at different structural levels of the programs and different times. After getting the results from the analysis, then the author indicates the gaps, which appeared during the evaluation process, and indicates what steps should be taken in order to improve the evaluation process of a strategic research program.